Memoria histórica de la rehabilitación del ferrocarril en Alausí entre los años 2008 y 2010 - Salgado Zurita, Alex Dario (2025)
The Alausí railway, an emblematic infrastructure project in Ecuador, underwent an ambitious rehabilitation process between 2008 and 2010. Its restoration not only revived a symbol of national progress but also reshaped the social and economic fabric of the Alausí canton. This study analyzes the historical memory of the local population and their perceptions of the impact of the railway on the community, adopting a qualitative approach that combines semi-structured interviews with residents, merchants, and local authorities, along with documentary and visual analysis. Findings indicate that the rehabilitation marked a new chapter for Alausí, positioning it as a key tourist destination and revitalizing the local economy through increased tourism-related ventures, job creation, and a strengthened sense of identity among residents. The railway became more than just a means of transportation; it emerged as a symbol of collective pride and hope for the future. However, the suspension of train operations in 2020 had a profound negative impact, resulting in income loss and reviving feelings of abandonment among the population. Despite this, the memory of the railway remains vivid, transcending its practical function to become a cultural emblem deeply rooted in community identity and shared experience. The study concludes that the rehabilitation of the railway was a milestone in Alausí recent history, with significant socio-economic and symbolic effects, though the closure of operations underscores the fragility of such projects in the absence of sustainable maintenance and management strategies.